ANALISIS PENURUNAN EMISI GAS RUMAH KACA DARI BANK SAMPAH DI KOTA PEKANBARU - Atiqatul Dzakirah; Suwondo Suwondo; Sri Wulandari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Domestic waste is one of the source of greenhouse gas emissions (GHG) that affect climate change. GHG emissions from the waste sector, including domestic solid waste are generally in the form of methane (CH4) generated from landfills (TPA) and carbon dioxide (CO2) generated from open burning activities. Waste banks have the potential to reduce GHG emissions because they reduce the generation of waste that will be disposed of in the TPA. This study aims to determine the level of reduction in greenhouse gas emissions from waste banks in Pekanbaru City. The research was conducted in Pekanbaru City from March to May 2021. The type of research used was descriptive quantitative research with a total sampling method covering 30 unit waste banks and 1 main waste bank managed by the Environment and Hygiene Service (DLHK) of Pekanbaru City. The data obtained were analyzed using the IPCC guidelines with accuracy level Tier1. The results showed that the waste bank in the city of Pekanbaru reduce GHG emissions amounted to 0.082 tons of CO2eq (8.37%) in the year 2019 and amounted to 0,018 tons of CO2eq (1.84%) in 2020.Key Words: Waste Banks, Reducing Greenhouse Gas Emissions, IPCC